The Implementation of Project-Based Learning in Enhancing Vocabulary Proficiency - Haerani; Ramadhan, Muh. Reza; Amin, Sulvahrul (PROJECT (Professional Journal of English Education), 2025)
This study aims to improve the vocabulary and pronunciation skills of seventh-grade English learners at UPTD SMPN 2 Barru by implementing a project-based learning (PjBL) model. Utilizing the Classroom Action Research (CAR) approach, this research unfolds over two cycles, where each cycle includes the phases of planning, execution, observation, and reflective analysis. Data collection involved tests, projects, and observational assessments to gauge student learning outcomes. The findings revealed a notable improvement in the average scores of students, rising from 62.92 in the initial cycle to 80.83 in the subsequent cycle. Furthermore, the proportion of students meeting completion criteria increased from 41.67% in the first cycle to 83.33% in the second cycle. Additionally, there was a marked enhancement in student participation, with learners demonstrating greater activity and confidence when presenting their work to the class. These outcomes suggest that the PjBL approach is effective in fostering student comprehension and engagement in English language learning. This study corroborates earlier research highlighting the advantages of PjBL, particularly in enhancing student motivation, collaboration, and academic performance. Consequently, it is recommended that strategies for implementing PjBL be meticulously crafted to optimize learning potential, cultivate a more conducive learning environment, and elevate students' academic success.